Effects of Vitamin E Administration on Platelet Function and Serum Lipid Peroxides in DOCA-Salt Hypertensive Rats - Umegaki, Keizo; Saegusa, Hiromi; Kurokawa, Masato; Ichikawa, Tomio (Thrombosis and Haemostasis, 1991)
Effects of vitamin E on platelet function and serum lipid peroxide levels were investigated in DOCA-salt hypertensive rats. In the hypertensive rats, ADP- and collagen-induced platelet aggregation in whole blood were markedly attenuated and accompanied by a reduction of serotonin content as compared with the normotensive controls. These facts indicated the appearance of exhausted platelets, which have already been activated in vivo, due to the hypertension. Platelet vitamin E levels were decreased by 50%, while serum lipid peroxide levels were increased 3.6-fold in the hypertensive rats. Vitamin E administration (10 times the dietary intake) during the experimental periods did not influence either the aggregability or the serotonin content of platelets from the hypertensive rats. However, vitamin E administration significantly prevented the elevation of serum tipid peroxides due to the hypertension. These results suggest that vitamin E administration has little effect on platelet activation in vivo due to DOCA-salt hypertension.